The itinerary of circulating miRNAs – implications for cancer progression and diagnosis (Journal of Medical Science, 2021)
microRNAs (miRNAs) are non-coding RNAs that regulate gene expression and protect cells from foreign nucleic acids. miRNA is produced in the nucleus and processed in the cytoplasm. These small nucleic acid molecules are released from cells to the extracellular matrix (extracellular miRNA, ex-miRNA) and reach blood plasma (circulating miRNA). Circulating miRNA can also be detected in other biological fluids, such as saliva, cerebrospinal fluid or urine, and it is usually carried by proteins or extracellular vesicles. Argonaute-miRNA, or miRNA-lipoprotein complex, protect miRNA from being degraded. The entrance of extracellular miRNA into a target cell is mediated by endocytosis and membrane fusion of extracellular vesicles. Additionally, miRNA can also be delivered in high-density lipoproteins by means of interactions with scavenger receptors. miRNAs absorbed into a cell can act as tumour promoters (oncomirs), or suppressors by inhibiting the translation process of the target mRNAs, thus, affecting cells in the tumour microenvironment. miRNA can impact other cells by supporting tumour growth, promoting angiogenesis and modulating the immune system. Molecular high-throughput methods are employed to detect circulating miRNA, and a potentially helpful diagnostic test has been designed to characterise the cancer type. In this review, we aim to summarise the itinerary of miRNAs from a source cell to a target cell, as well as to show how this class of small nucleic acids participates in intercellular communication. Finally, we highlight examples of miRNAs usage as potential molecular markers and discuss treatment approaches in clinical trials.